Calorimetry of isolated hearts (ii) energetic of ca 2+ homeostasis in different animal models and during ischemia – reperfusion - Consolini, Alicia Elvira (2017)
Calorimetry has been applied to skeletal and cardiac muscle from many years ago, andthere were intents to calculate the heat fractions associated to basal metabolism (restingheat rate, Hr) and the active heat (Ha). This review explains the principles and evolution of cardiac energetic, measured by calorimetry and the advantages with respect to the measurement of oxygen consumption. Moreover, the methods to estimate separately the fractions of tension-dependent (TDH) and tension-independent heat (TIH) were described, as well as the characterization of each one. A method to determine 4 heat components in a single beat in the presence of contraction in perfused rat ventricles was revised, as well as the properties of the long-duration fourth fraction not previously seen with other methods.The advantages and limitations of each method were analyzed. Calorimetry allows toevaluate the occurrence degree of certain exothermic processes such as ionic fluxes can be studied by comparing the heat released with the energetic equivalent and the stoichiometry of the process with the ATP hydrolysis. Calorimetry is a sensitive and useful methodology to evaluate the ?in situ? incidence of exothermic mechanisms in the heart.